Study of antimycobacterial, cytotoxic, and mutagenic potential of polymeric nanoparticles of copper (II) complex - Aleixo, Nadia Andrade; Gomes, Pietra Stefany da Silva; Silva, Patrícia Bento da [UNESP]; Sato, Mariana Rillo [UNESP]; Campos, Débora Leite [UNESP]; Barud, Hernane da Silva; Castro, Guillermo Raul; Islan, German Abel; Toledo, Constanza; Karp, Federico; Chorilli, Marlus [UNESP]; Pavan, Fernando Rogério [UNESP]; et al. (My University, 2022)
This study aimed to encapsulate and characterise a potential anti-tuberculosis copper complex (CuCl2(INH)2.H2O:I1) into polymeric nanoparticles (PNs) of polymethacrylate copolymers (Eudragit®, Eu) developed by nanoprecipitation method. NE30D, S100 and, E100 polymers were tested. The physicochemical characterisations were performed by DLS, TEM, FTIR, encapsulation efficiency and, in vitro release studies. Encapsulation of I1 in PN-NE30D, PN-E100, and PN-S100 was 26.3%, 94.5%, 22.6%, respectively. The particle size and zeta potentials were 82.3 nm and −24.5 mV for PNs-NE30D, 304.4 nm and +18.7 mV for PNs-E100, and 517.9 nm and −6.9 mV for PNs-S100, respectively. All PDIs were under 0.5. The formulations showed an I1 controlled release at alkaline pH with 29.7% from PNs-NE30D, 7.9% from PNs-E100 and, 28.1% from PNs-S100 at 1 h incubation. PNs were stable for at least 3 months. Particularly, PNs-NE30D demonstrated moderate inhibition of M. tuberculosis and low cytotoxic activity. None of the PNs induced mutagenicity.
Keywords: Copper(II) complexes; Eudragit®; mutagenicity; polymeric matrices; resazurin assay